LN Monocytes Limit DC-Poly I:C Induced Cytotoxic T Cell Response via IL-10 and Induction of Suppressor CD4 T Cells - Tewari, Anita; Prabagar, Miglena G.; Gibbings, Sophie L.; Rawat, Kavita; Jakubzick, Claudia V. (Frontiers in Immunology, 2021)
Every immune response has accelerators and brakes. Depending on the pathogen or injury, monocytes can play either role, promoting or resolving immunity. Poly I:C, a potent TLR3 ligand, licenses cross-presenting dendritic cells (DC1) to accelerate a robust cytotoxic T cells response against a foreign antigen. Poly I:C thus has promise as an adjuvant in cancer immunotherapy and viral subunit vaccines. Like DC1s, monocytes are also abundant in the LNs. They may act as either immune accelerators or brakes, depending on the inflammatory mediator they encounter. However, little is known about their contribution to adaptive immunity in the context of antigen and Poly I:C. Using monocyte-deficient and chimeric mice, we demonstrate that LN monocytes indirectly dampen a Poly I:C induced antigen-specific cytotoxic T cell response, exerting a “braking” function. This effect is mediated by IL-10 production and induction of suppressor CD4+ T cells. In a metastatic melanoma model, we show that a triple-combination prophylactic treatment consisting of anti-IL-10, tumor peptides and Poly I:C works because removing IL-10 counteracts the monocytic brake, resulting in significantly fewer tumors compared to mice treated with tumor peptides and Poly I:C alone. Finally, in human LN tissue, we observed that monocytes (unlike DCs) express high levels of IL-10, suggesting that anti-IL-10 may be an important addition to treatments. Overall, our data demonstrates that LN monocytes regulate the induction of a robust DC1-mediated immune response. Neutralization of either IL-10 or monocytes can augment Poly I:C-based treatments and enhance T cell cytotoxicity.